Хід росту штучних модальних соснових деревостанів Придонецького Степу та використання ними лісорослинного потенціалу - Prihodko, O. B.; Pasternak, V. P. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2023)
Introduction In today's environment, the issue of developing regulatory and information materials for evaluation and forecasting of the growth of modal stands is relevant, taking into account zonal features. Such standards will allow evaluation of forest ecosystem functions and control the efficiency of forest management. Scots pine (Pinus sylvestris L.) is one of the most resilient tree species in the steppe conditions. The pine stands in Prydonetskyi Steppe have certain features and require detailed research. The study aimed to reveal the features of the growth and productivity of artificial modal pine stands in Prydonetskyi Steppe in Ukraine. Materials and Methods To develop growth tables, information from the compartment database “Forest fund of Ukraine” of the Ukrainian State Forest Management Planning Association Ukrderzhlisproekt for Izyum Forest State Enterprise, Lyman Forest State Enterprise, and Kreminna Forest and Hunting State Enterprise, mensuration data on 26 sample plots in pine stands and observations on four monitoring plots were used. In addition, five sample plots were used, which were laid during the forest management planning in Lyman Forest State Enterprise in Donetsk region, with felling and measuring 15 model trees. The sites were located mainly in fresh poor (A2) and relatively poor (B2) forest site conditions, as well as dry poor (A1) and fresh relatively rich (C2) site conditions. The efficiency of the use of forest cite capacity of forest lands by modal stands was quantitatively assessed using an indicator of productivity of native stands according to I. Turkevych. The forests of the studied enterprises are dominated by Scots pine stands, which grow on 58% of the forest areas covered with forest vegetation. Most often pine stands have a medium density of stocking and II and I site classes. The prevailing forest types are fresh poor pine, relatively poor oak-pine, and dry poor pine types. Average tree heights were approximated using the Mitscherlich function. The transition from relative to absolute values was based on the basic height values of the modified scale of Orlov for 80-year-old stands of seed origin. An allometric function was used to model the average diameter, including the age and height of the stand. The growing stock was calculated using Mitscherlich formula depending on the height and relative density of the stocking. The dynamics of the relative density of stocking was modeled using a second-order polynomial. Results The height growth of modal pine stands of artificial origin occurs within one site index class of the general site index scale, although at a younger age, they tend to slow growth. The stands of the Prydonetskyi Steppe had a slightly more intensive growth in height at the age of 20–30 years with its subsequent slowing down, smaller diameters due to a bigger relative density of stocking, and, accordingly, a bigger growing stock compared to the modal pine stands of Dnieper Northern Steppe according to V.  Lovynska. Middle-aged and premature modal pine stands are characterized by a relatively high degree of forest site capacity use compared to fresh poor pine site conditions in the Steppe. The lowest values of forest site capacity were found in the first and second age classes (41–61%). Conclusions The studied modal pine forests of fresh poor site condition grow mainly according to the II site class and had rather high productivity, taking into account the unfavorable forest site conditions. This is evidenced by their growing stock, which at the age of 90 was about 330 m3 ·ha-1 and a relatively high degree of use of forest site capacity – 74%. Quantitative maturity of artificial pine stands of Prydonetskyi Steppe occurs at the age of 60. The developed regional growth tables objectively characterize the dynamics; they consider regional features of growth and formation of modal pine stands of Prydonetskyi Steppe and can serve as a basis for solving scientific and practical forestry tasks. 2 Figs., 4 Tables, 17 Refs.